„Ludzkie ciało jest najlepszym obrazem ludzkiej duszy”. Cavell i Wittgenstein o innych umysłach - Dehnel, Piotr (Bogucki Wydawnictwo Naukowe; Wydawnictwo Naukowe Wydziału Filozoficznego Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2025)
W artykule podejmuję problem innych umysłów w interpretacji Stanleya Cavella i Ludwiga Wittgensteina. Obaj reprezentowali pogląd, że cudze stany mentalne są nam dostępne bezpośrednio. Według Cavella mimo tej bezpośredniości nasza wiedza o innych umysłach obarczona jest nieusuwalnym sceptycyzmem, ponieważ nie może być niczym innym jak tylko „empatyczną projekcją”. Wittgenstein natomiast nie chce wyjaśniać, w jaki sposób poznajemy cudze stany mentalne, ale tak opisać użycie wyrażeń odnoszących się do tych stanów, by nie było potrzeby stawiania filozoficznych pytań o inne umysły. In this article, I discuss the concept of ‘other minds’, as interpreted by Stanley Cavell and Ludwig Wittgenstein. Both philosophers held the view that other people’s mental states are directly accessible to us. However, according to Cavell, despite this directness, our knowledge of other minds is burdened with irremovable scepticism because it can only ever be an ‘empathic projection’. In contrast, Wittgenstein does not seek to explain how we know about other people’s mental states; rather, he aims to describe the use of expressions that refer to these states in such a way that there is no need to ask philosophical questions about other minds.
“The human body is the best picture of the human soul.” Cavell and Wittgenstein on Other Minds
Keywords: umysł; wiedza; sceptycyzm; gramatyka; pierwsza i trzecia osoba; mind; knowledge; skepticism; grammar; first and third person